HRM 4.0 For Human-Centered Organizations - Bissola, Rita, editor 647018; Imperatori, Barbara, editor 647019; Emerald Publishing Limited (Online service) issuing body 646680 (Bingley, U.K. : Emerald Publishing Limited, 2019)
Offering researchers and professionals cutting-edge research and practical guidelines to turn the challenging scenario of Industry 4.0 into a successful transformation for the HRM domain, this volume focuses on three critical insights: HRM in the 4.0 era, job design for the smart economy, and HRM tools for digital transformation.